Open-source enterprise resource planning systems for small and medium enterprises: a conceptual framework / Kazeem Sulaimon, Ehsan Fansuree Surin and Muhammad Iskandar Hamzah - Sulaimon, Kazeem; Surin, Ehsan Fansuree; Hamzah, Muhammad Iskandar (Faculty of Business and Management ; UiTM Press, 2024)
The growing importance of information management in the digital economy has exerted considerable pressure on small and medium enterprises (SMEs) to implement advanced innovations in technology. Nonetheless, the high costs and intricacy of conventional Enterprise Resource Planning (ERP) systems have constrained their uptake among SMEs. This conceptual study examines the feasibility of Open-Source ERP (OS-ERP) systems as a practical option for Malaysian SMEs, offering a conceptual framework that connects information management capabilities, entrepreneurial orientation (EO), and enterprise success. The article contends that OS-ERP systems can augment entrepreneurial performance by enhancing information integration, strategic decision-making, and enterprise agility. This approach seeks to guide future research and offer practical insights for SMEs and policymakers to encourage digital transformation.